The Influence of Monday-Thursday Fasting Intensity on the Patience of Islamic Religious Education Students - Syahris Shidiq; Shittu Abdulazeez Balogun; Saeed Namazi Zadegan (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: This study aims to reveal whether there is a correlation between the intensity of performing the Monday Thursday sunnah fast and the level of patience of Islamic Religious Education students. Methodology: The research method uses a quantitative approach. The population of this study was 153 students of Islamic Religious Education. The sample in this study was 40 students. The researcher used a data collection method in the form of a questionnaire. Instrument analysis includes validity and reliability analysis. Then process the data that has been obtained using the product moment formula. Main Findings: The results of this study indicate that the Intensity of Carrying Out Sunnah Fasting on Mondays and Thursdays is in the good category as indicated by an average value of 77.47. Meanwhile, the Level of Patience of Islamic Religious Education Students is included in the sufficient category as indicated by an average value of 74.45. Novelty/Originality of this study: This study can reveal how routine spiritual practices have a significant influence in shaping the character of patience among young academics.